Respiratory Physiotherapy Management in Pediatric Bronchial Asthma - Dika Apriani; Wahyu Tri Sudaryanto; Fatonah Sulistyowati (Asosiasi Dosen Muda Indonesia, 2026)
Bronchial asthma is a chronic inflammatory disease of the respiratory tract characterized by airway narrowing, bronchial hyperresponsiveness, and reversible airflow limitation. This condition may cause symptoms such as dyspnea, coughing, wheezing, and reduced functional activity capacity, particularly in pediatric patients. Therefore, supportive interventions such as respiratory physiotherapy are important to improve respiratory function and reduce asthma symptoms. Objective: This study aims to describe the effectiveness of respiratory physiotherapy management in a pediatric patient with bronchial asthma treated at RSUP Surakarta and to highlight the role of physiotherapy as a complementary intervention in improving respiratory function. Method: This study used a qualitative case report design involving a five-year-old boy diagnosed with bronchial asthma. Data were collected through clinical examination and repeated evaluations during five physiotherapy sessions, including thoracic expansion measurement, peak expiratory flow assessment, auscultation examination, vital sign monitoring, and dyspnea assessment using the Borg Scale and the Modified Medical Research Council (mMRC) scale. Data were analyzed descriptively by comparing the patient’s clinical condition before and after intervention across treatment sessions. Findings: The results showed improvement in several respiratory indicators after the intervention. Thoracic expansion increased at all measurement points, peak expiratory flow improved from 200 L/min to 550 L/min, and breath sounds changed from wheezing and rhonchi to normal vesicular sounds. In addition, vital signs showed improvement and perceived dyspnea decreased based on the Borg Scale, although the mMRC score remained unchanged. Implications: These findings suggest that respiratory physiotherapy may contribute to improving ventilation, chest wall mobility, and respiratory efficiency in pediatric asthma patients. Physiotherapy interventions can therefore be considered as supportive therapy in comprehensive asthma management. Originality: The originality of this study lies in the detailed clinical documentation of multimodal respiratory physiotherapy interventions in a pediatric bronchial asthma case, particularly in evaluating changes in thoracic expansion, peak expiratory flow, auscultation findings, and dyspnea during repeated treatment sessions.